1998
DOI: 10.1016/s0741-5214(98)70233-2
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein thrombophlebitis (SVT): A deceptively benign disease

Abstract: The incidence of the hypercoagulable state in patients with SVT is high. Thirty-five percent of patients with isolated SVT had consistently abnormal coagulation profiles. Patients with SVT may be prone to the development of DVT or saphenofemoral junction thrombophlebitis and should be closely followed after the initial diagnosis of hypercoagulability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…1) Malignancy was also reported to have a weak association with superficial thrombophlebitis. 1) Patients with superficial thrombophlebitis should be screened for hypercoagulability because of their high prevalence of hypercoagulable states caused by a deficiency in antithrombin III or abnormalities in protein C and S. 1,13) Male gender, history of thromboembolism, severe venous insufficiency, and shorter interval between symptom onset and diagnosis (less than 7 days) are also reported to be risk factors associated with complications after superficial vein thrombosis. 12) In this study, Protein C deficiency, hormone therapy, malignancy, and driving as an occupation were found to increase the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…1) Malignancy was also reported to have a weak association with superficial thrombophlebitis. 1) Patients with superficial thrombophlebitis should be screened for hypercoagulability because of their high prevalence of hypercoagulable states caused by a deficiency in antithrombin III or abnormalities in protein C and S. 1,13) Male gender, history of thromboembolism, severe venous insufficiency, and shorter interval between symptom onset and diagnosis (less than 7 days) are also reported to be risk factors associated with complications after superficial vein thrombosis. 12) In this study, Protein C deficiency, hormone therapy, malignancy, and driving as an occupation were found to increase the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hanson et al reported that, among patients with saphenous vein thrombosis and DVT, 35% of those had abnormal coagulation profiles, 13) suggesting that examination of coagulation profiles is necessary in varicose vein patients with STP.…”
Section: Prevalence Of Asymptomatic Dvt In Varicose Vein Patients Witmentioning
confidence: 99%
“…The incidence of thrombophilia is also increased in patients with SVT [ 10,13,[15][16][17] . It may be useful to evaluate patients with SVT who do not have varicose veins and have one other risk factor for SVT for markers of thrombophilia including protein S de fi ciency, protein C de fi ciency, anticardiolipin antibodies, beta2 glycoprotein, factor V Leiden, prothrombin mutation, antithrombin de fi ciency, lupus anticoagulant, methylene tetrahydrofolate reductase de fi ciency, and fasting serum homocysteine [ 10,13,16,[18][19][20] .…”
Section: Epidemiology and Etiologymentioning
confidence: 99%
“…All patients received enoxaparin (0.1 mL/10 kg) and elastic compression for treatment period Hanson (1998) [ 15 ] Open (N = 17) Anticoagulation is mandatory in patients with SVT when DVT is present. Anticoagulation is also often used when a thrombus is found in the SPJ or SFJ or extends as free fl oating in the CFV or popliteal veins.…”
Section: Treatmentmentioning
confidence: 99%